2021
DOI: 10.1016/s2214-109x(21)00434-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology and the role of international and regional travel in the SARS-CoV-2 epidemic in Zimbabwe: a retrospective study of routinely collected surveillance data

Abstract: Background Advances in SARS-CoV-2 sequencing have enabled identification of new variants, tracking of its evolution, and monitoring of its spread. We aimed to use whole genome sequencing to describe the molecular epidemiology of the SARS-CoV-2 outbreak and to inform the implementation of effective public health interventions for control in Zimbabwe. Methods We performed a retrospective study of nasopharyngeal samples collected from nine laboratories in Zimbabwe between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Our study contributes to improved understanding on SARS-CoV-2 introduction and transmission patterns in sub-Saharan Africa countries ( Bugembe et al, 2020 ; Butera et al, 2021 ; Githinji et al, 2021 ; Mashe et al, 2021 ; Wilkinson et al, 2021 ). This knowledge has potential to inform the application of future mitigation strategies especially in light of the growing evidence that SARS-CoV-2 will be endemic in human populations ( Planas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…Our study contributes to improved understanding on SARS-CoV-2 introduction and transmission patterns in sub-Saharan Africa countries ( Bugembe et al, 2020 ; Butera et al, 2021 ; Githinji et al, 2021 ; Mashe et al, 2021 ; Wilkinson et al, 2021 ). This knowledge has potential to inform the application of future mitigation strategies especially in light of the growing evidence that SARS-CoV-2 will be endemic in human populations ( Planas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…A study from Zimbabwe of the genomic epidemiology of the SARS-CoV-2 variants found that 60% of cases were imported, indicating that human movement is a key factor in its transmission, further supporting the importance of quarantine and restriction of human movements. 2 Rational development of COVID-19 vaccines also relies on mass-spectrometry (MS)-based characterization of the spike (S) glycoprotein of the virus, whose conformational dynamics is key for vaccine design. The viral S protein interacts with ACE2 on host cells, and antibodies that interfere with this by targeting the S protein can potentially neutralize the virus.…”
Section: Main Textmentioning
confidence: 99%
“…A study about COVID-19 and SARS-CoV-2 in Zimbabwean patients has been done by Mashe et al . 2021, however the study was more focussed on the epidemiology of COVID-19.…”
Section: Introductionmentioning
confidence: 99%